2017
DOI: 10.1097/igc.0000000000001014
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adjuvant Chemotherapy, Radiation Therapy, or Combined Modality Therapy and the Impact on Survival for Uterine Carcinosarcoma Limited to the Pelvis

Abstract: Combination therapy with CT and RT was associated with significantly improved 5-year OS compared with no further therapy, RT alone, or CT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…This aligns with prior studies using NCDB, which reported 36% − 42% of UCS patients receiving no adjuvant treatment. Notably these NCDB studies included patients of all ages and included either patients from stage I only ( Seagle et al, 2017 ), or stage I-III ( Wong et al, 2017 , Stokes et al, 2018 , Rauh-Hain et al, 2015 ). In our SEER-Medicare population, we found that women who did not receive treatment were generally older, more frequently Black, with higher comorbidity indices, lower income, and resided in the West.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This aligns with prior studies using NCDB, which reported 36% − 42% of UCS patients receiving no adjuvant treatment. Notably these NCDB studies included patients of all ages and included either patients from stage I only ( Seagle et al, 2017 ), or stage I-III ( Wong et al, 2017 , Stokes et al, 2018 , Rauh-Hain et al, 2015 ). In our SEER-Medicare population, we found that women who did not receive treatment were generally older, more frequently Black, with higher comorbidity indices, lower income, and resided in the West.…”
Section: Discussionmentioning
confidence: 99%
“…Highest five-year survival was observed after brachytherapy and multiagent chemotherapy (74.1% (68.3–80.3%), P < 2.0 × 10(–16)). Several other NCDB based studies have reported upon UCS patients in aggregate, including those from stage I-IV ( Rauh-Hain et al, 2015 , Odei et al, 2018 ) or I-III ( Wong et al, 2017 ). Rauh-Jain et al, identified that stage I-II UCS patients receiving combination therapy had significantly improved OS compared to no treatment (HR 0.55, 96 %CI 0.46–0.66, p = not provided), as well as chemotherapy only (HR 0.73, 95% CI 0.60–0.88), whereas radiation alone did not (HR.90, 95% CI 0.80–1.02) ( Rauh-Hain et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study from the Netherlands [12], consisting of 1140 cases of CS, proved that adjuvant treatment, whether chemotherapy, radiotherapy or both, improved OS, especially if lymph node dissection was not performed or if the lymph nodes were infiltrated. Wong et al [13] analysed 4906 CS patients and found that the impact of both adjuvant chemotherapy and radiotherapy on OS was greater than the impact of each modality alone and better than no adjuvant at all. Unfortunately, we did not have a sufficient number of patients in the present study to assess the impact of adjuvant treatment on survival.…”
Section: Discussionmentioning
confidence: 99%
“…A biologically equivalent conventionally fractionated radiotherapy scheme (2 Gy/fraction regimen) demands 21 days of therapy (30 days), thus our regimen reduced the overall radiotherapy external beam treatment time by 11 days. The radiobiological methods applied for calculation of the NTD have been previously reported (15,16).…”
Section: Methodsmentioning
confidence: 99%